Pharmacokinetic and safety profile of tofacitinib in children with polyarticular course juvenile idiopathic arthritis: results of a phase 1, open-label, multicenter study - Nicolino Ruperto; Hermine I. Brunner; Zbigniew Zuber; Nikolay Tzaribachev; Daniel J. Kingsbury; Ivan Foeldvari; Gerd Horneff; Elzbieta Smolewska; Richard K. Vehe; Anasuya Hazra; Rong Wang; Charles A. Mebus; et al. (BMC, 2017)
Abstract Background Juvenile idiopathic arthritis (JIA) is the most common pediatric rheumatic disease and a leading cause of childhood disability. The objective of this study was to characterize the PK, safety, and taste acceptability of tofacitinib in patients with JIA. Methods This Phase 1, open-label, multiple-dose (twice daily [BID] for 5 days) study of tofacitinib in patients with active (≥ 5 joints) polyarticular course JIA was conducted from March 2013-December 2015. Patients were allocated to one of three age-based cohorts: Cohort 1, 12 to < 18 years; Cohort 2, 6 to < 12 years; and Cohort 3, 2 to < 6 years. Tofacitinib was administered according to age and body weight as tablets or oral solution (grape flavor). PK were assessed on Day 5; safety was assessed at screening, Day 1, and Day 5. Taste acceptability of the oral solution was evaluated. Results Twenty-six patients (age range 2-17 years) were enrolled: Cohort 1, N = 8; Cohort 2, N = 9; Cohort 3, N = 9; median tofacitinib doses were 5.0, 2.5, and 3.0 mg BID, respectively. The higher median tofacitinib dose in Cohort 3 versus Cohort 2 reflected implementation of an amended dosing scheme following an interim PK analysis after Cohort 2 recruitment. Geometric mean AUC at steady state (AUCtau) was 156.6 ng•h/mL in Cohort 1, 118.8 ng•h/mL in Cohort 2, and 142.5 ng•h/mL in Cohort 3; Cmax (ng/mL) was 47.0, 41.7, and 66.2, respectively. Ctrough, Cmin, and t1/2 were similar in Cohorts 2 and 3, but higher in Cohort 1. Median time to Cmax (Tmax) was similar between cohorts. Apparent clearance and volume of distribution decreased with decreasing age. Tofacitinib was well tolerated, with no serious adverse events or discontinuations due to adverse events reported. Taste acceptability was confirmed. Conclusions PK findings from this study in children with polyarticular course JIA established dosing regimens and acceptable taste for use in subsequent studies within the tofacitinib pediatric development program. Trial registration ClinicalTrials.gov: NCT01513902 .